A study of the perception of situation-bound utterances as culture-specific pragmatic units by Russian learners of English. (August 2018) - Kecskes, Istvan; Obdalova, Olga; Minakova, Ludmila; Soboleva, Aleksandra
Abstract: The present paper considers situation-bound utterances (SBU) as culture-specific pragmatic units of speech. It investigates how SBUs in English are processed by Russian learners of English as a foreign language. The focus of our inquiry is on three issues. First, we intend to identify the reasons of difficulties of our subjects in comprehending and using SBUs. Second, we aim to explore how the interplay of prior context and actual situational context affects SBU interpretation. Third, we will analyze the extent to which pragmatic strategies such as compositionality (COM), closeness to own culture (CLO), and actual situational context (SIT) will help students comprehend and infer the actual meanings of situation-bound utterances in two organized ways of their delivery – contextual and isolated. One of the advantages of the data collection procedures was that most of the activities and tasks were combined with some training, awareness raising, learning activities and discussions which gave us not only insights into the cognitive processes responsible for acquisition of SBUs in Russian learners of English but also helped our subjects develop their knowledge about the functions and use of these very important pragmatic idioms.